4a^2b^3+ab^4-4ab^4-b^5=

Simple and best practice solution for 4a^2b^3+ab^4-4ab^4-b^5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a^2b^3+ab^4-4ab^4-b^5= equation:


Simplifying
4a2b3 + ab4 + -4ab4 + -1b5 = 0

Reorder the terms:
ab4 + -4ab4 + 4a2b3 + -1b5 = 0

Combine like terms: ab4 + -4ab4 = -3ab4
-3ab4 + 4a2b3 + -1b5 = 0

Solving
-3ab4 + 4a2b3 + -1b5 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), 'b3'.
b3(-3ab + 4a2 + -1b2) = 0

Factor a trinomial.
b3((a + -1b)(4a + b)) = 0

Subproblem 1

Set the factor 'b3' equal to zero and attempt to solve: Simplifying b3 = 0 Solving b3 = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b3' to each side of the equation. b3 + -1b3 = 0 + -1b3 Remove the zero: 0 = -1b3 Simplifying 0 = -1b3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(a + -1b)' equal to zero and attempt to solve: Simplifying a + -1b = 0 Solving a + -1b = 0 Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. a + -1b + b = 0 + b Combine like terms: -1b + b = 0 a + 0 = 0 + b a = 0 + b Remove the zero: a = b Simplifying a = b

Subproblem 3

Set the factor '(4a + b)' equal to zero and attempt to solve: Simplifying 4a + b = 0 Solving 4a + b = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 4a + b + -1b = 0 + -1b Combine like terms: b + -1b = 0 4a + 0 = 0 + -1b 4a = 0 + -1b Remove the zero: 4a = -1b Divide each side by '4'. a = -0.25b Simplifying a = -0.25b

Solution

a = {b, -0.25b}

 

See similar equations:

| -28=4(u-3)-8u | | 3(y+7)-6y=-6 | | -6x+14=-8(x-3) | | 8x=7x-18 | | 28n^4+16x^3-80x^2= | | -7(x+6)=-3x-14 | | -6x+3y=120 | | -4x+2=x+23 | | 9u+39=-6(u+6) | | 72x^2-492x+840=0 | | -6w-13=5(w+4) | | x^2-12x=-10 | | 3y-2x-3=0 | | 125+8= | | 1.2x-0.8=0.8+0.4 | | 3x^3-5x^2+2x= | | 6z-7=3 | | 7x^2-32x-60= | | 30x^2y-87xy+30y= | | -4(y+6)+2(y+2)=18 | | x^3-23x^2+176x-448=0 | | 9r^2-5r-10= | | 80-3x=15x+24 | | -3(2x-4x)+4=-4(5x-3x+1)+10+13x | | 9-7x=73-35x | | 9p^2r+73pr+70r= | | 4=3(-9y-5)-8y | | 3f+6=6f-18 | | 4x^3+43x^2+30x= | | 10m^2+89m-9= | | =2x^3*x | | W^2=16w | | =2x^3*x^2 | | =(0.1x^2+0.3x+1) | | 28=5x-(3x+12) | | 3*x^2-11*x+6=0 | | 6y-4=0 | | 12-5x=-2x-2 | | 35-7x=2x+16 | | 0=-16x^2+2x+10 | | -(5y+2)-(-4y-3)=-3 | | 12a+4=0 | | 3a-1=0 | | X^2+12x+8=0 | | 8x-24=5x | | -8(t-9)+(t+33)=1 | | -8(t-9)+(t+3)=1 | | 6x+94=15x-14 | | 5x+6=-64-9x | | 1.10x+0.40(200-x)=0.54(200) | | 7x+12=4x-17 | | 7-9x=155-37x | | 5x=4x+12 | | 175-2x=23x+15 | | 3x-25=x-5 | | 2m^2+17m+14=0 | | 9x+6=8x | | 50x+100=100x | | 4x+2=3x+3 | | 9y-2=8y | | 3.14*11*11= | | 5x+13=10x+12 | | 5a^2+13a+6=0 | | 12x-10=-11+9x | | 9x-27=45 |